2008
DOI: 10.1213/01.ane.0000277493.42335.7b
|View full text |Cite
|
Sign up to set email alerts
|

Acupuncture Analgesia: I. The Scientific Basis

Abstract: Acupuncture has been used in China and other Asian countries for the past 3000 yr. Recently, this technique has been gaining increased popularity among physicians and patients in the United States. Even though acupuncture-induced analgesia is being used in many pain management programs in the United States, the mechanism of action remains unclear. Studies suggest that acupuncture and related techniques trigger a sequence of events that include the release of neurotransmitters, endogenous opioid-like substances… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
126
0
10

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 232 publications
(137 citation statements)
references
References 61 publications
1
126
0
10
Order By: Relevance
“…Activation of the hypothalamus triggers release of endorphins and allows for systemic pain relief. 9,16 Mechanistically, Cheng suggested that the specific effects of electrical stimulation may be a function of the frequency of electrical stimulation. 17 Reports about mice suggest that different receptors appear to be stimulated by different currents, with low frequencies between 2 and 15 Hz activating endorphin pathways, while higher frequencies may lead to release of norepinephrine and/or serotonin without analgesia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Activation of the hypothalamus triggers release of endorphins and allows for systemic pain relief. 9,16 Mechanistically, Cheng suggested that the specific effects of electrical stimulation may be a function of the frequency of electrical stimulation. 17 Reports about mice suggest that different receptors appear to be stimulated by different currents, with low frequencies between 2 and 15 Hz activating endorphin pathways, while higher frequencies may lead to release of norepinephrine and/or serotonin without analgesia.…”
Section: Discussionmentioning
confidence: 99%
“…Noninvasive acupuncture was applied, using four self-adhesive electrodes to the baby's lower extremities at the following acupuncture points: Zusanli (ST 36); Sanyinjiao (SP 6); Taixi (KI 3); and Kunlun (BL 60). [6][7][8][9] The placement of the electrodes was determined by an anesthesiologist who had acupuncture experience. The TENS unit was turned on and the infant received NESAP for 10 minutes prior to the heel stick.…”
Section: Yates Et Almentioning
confidence: 99%
“…electro-acupuncture (EA), or standard care without acupuncture (SC). The study protocol followed the CONSORT [24] and STRICTA [25] recommendations and the rationale of acupuncture was based on Western medical theories [26][27][28]. A full description of the study design [23] and the primary results have been published previously [7], and the trial was registered at ClinicalTrials.gov: NCT01197950.…”
Section: Methodsmentioning
confidence: 99%
“…[1] Transcutaneous Electrical Nerve Stimulation (TENS) stimulates nerve endings by electrical stimulation and works on gate theory of pain relief. [2] The analgesic effect of TENS has been found to be dependent on duration, intensity, frequency of stimulation and location of electrodes. [3] While previous systemic review, Reeve et al concluded that there is little if any evidence in favour of TENS for postoperative analgesia.…”
Section: Introductionmentioning
confidence: 99%